Simulation in the Continuing Professional Development of Academic Emergency Physicians: A Canadian National Survey. Issue 4 (August 2021) - Forristal, Chantal; Russell, Evan; McColl, Tamara; Petrosoniak, Andrew; Thoma, Brent; Caners, Kyla; Mastoras, George; Szulewski, Adam; Chaplin, Timothy; Huffman, James; Woolfrey, Karen; Dakin, Christa; et al.
Abstract : Introduction: Simulation is becoming a popular educational modality for physician continuing professional development (CPD). This study sought to characterize how simulation-based CPD (SBCPD) is being used in Canada and what academic emergency physicians (AEPs) desire in an SBCPD program. Methods: Two national surveys were conducted from March to June 2018. First, the SBCPD Needs Assessment Survey was administered online to all full-time AEPs across 9 Canadian academic emergency medicine (EM) sites. Second, the SBCPD Status Survey was administered by telephone to the department representatives (DRs)—simulation directors or equivalent—at 20 Canadian academic EM sites. Results: Response rates for the SBCPD Needs Assessment and the SBCPD Status Survey were 40% (252/635) and 100% (20/20) respectively. Sixty percent of Canadian academic EM sites reported using SBCPD, although only 30% reported dedicated funding support. Academic emergency physician responses demonstrated a median annual SBCPD of 3 hours. Reported incentivization for SBCPD participation varied with AEPs reporting less incentivization than DRs. Academic emergency physicians identified time commitments outside of shift, lack of opportunities, and lack of departmental funding as their top barriers to participation, whereas DRs thought AEPs fear of peer judgment and inexperience with simulation were substantial barriers. Content areas of interest for SBCPD were as follows: rare procedures, pediatric resuscitation, and neonatal resuscitation. Lastly, interprofessional involvement in SBCPD was valued by both DRs and AEPs. Conclusions: Simulation-based CPD programs are becoming common in Canadian academic EM sites. Our findings will guide program coordinators in addressing barriers to participation, selecting content, and determining the frequency of SBCPD events. Abstract : Supplemental digital content is available in the text.